Building School Optimism and Responsibility in Quality Education - Sofiawati, Esmi Tsalsa; Sujanto, Bedjo; Suryadi, Suryadi (International Conference on Elementary Education, 2020)
Education is now growing rapidly and is able to influence a variety of life arrangements. All parties are involved in it to keep abreast of the times . Therefore , optimism is needed in responding to these challenges, and the responsibility of schools as educational institutions capable of determining quality education . This study tried to take photos of how the school was able to air the effort to build optimism and responsibility in conducting education towards a better match expectations. This study uses a qualitative approach with case study method. The results of the research conducted revealed that in realizing quality education there are things that schools do that are inseparable from 8 interrelated educational standards between one and the other. Therefore in this case the school emphasizes more on graduate competency standards and process standards as a portrait of building optimism and a sense of responsibility